Copolyester resin and method for producing the same
By designing a copolyester resin containing specific structural units, the problem of insufficient degradability and thermoformability of existing resins in seawater is solved, and the feasibility of polymerization and processing at high temperatures is achieved. It is suitable for packaging materials and films and other products.
Patent Information
- Application Number
- JP2024190724
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-06-27
AI Technical Summary
The copolyester resin in the prior art lacks degradability and thermal forming properties in seawater, and the synthesis of high molecular weight bodies is limited, making it difficult to meet the needs of high temperature polymerization and processing.
By designing a copolyester resin containing specific structural units, a combination of a variety of dibasic acids and diols is used to form structural units with different degradability and thermoformability, ensuring that the resin has a degradation rate of more than 15% in seawater and can be polymerized and thermoformed at high temperatures.
It realizes the efficient degradability and good thermoformability of copolyester resin in seawater, and is suitable for the production of packaging materials and films.
Smart Images

Figure 2025020252000001 
Figure 2025020252000002 
Figure 2025020252000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolyester resin and a method for producing the same. [Background technology]
[0002] Many synthetic resins do not decompose easily in the natural environment. Therefore, the deterioration of the natural environment caused by synthetic resins has become a problem. For example, discarded synthetic resins are broken or scraped by the ultraviolet rays of the sun and waves in the ocean, and eventually become microplastics, destroying and polluting the marine environment of plants and animals.
[0003] In response to the social issue of environmental degradation caused by the mass disposal of synthetic resins, there is a growing demand for sustainable products (packaging materials, films, etc.) made from resins that are biodegradable in all environments (seawater, freshwater, soil, compost, etc.).
[0004] An example of a resin that is biodegradable in any environment is polyhydroxyalkanoate (PHA). PHA has attracted attention as an environmentally friendly resin, and is widely used, with a demand for further expansion of its application range.
[0005] However, PHA has a low thermoformability compared to general-purpose resins because its melting temperature and thermal decomposition temperature are close, and thermal decomposition progresses during processing. In addition, when synthesizing PHA from monomers by chemical polymerization, it is difficult to synthesize high molecular weight polymers because the upper limit of the polymerization temperature is low. Therefore, there is a demand for biodegradable resins that can be polymerized at relatively high temperatures similar to those of general-purpose resins and that can be thermoformed.
[0006] In order to solve the above problems, a technique has been reported in which a specific chemical structure is introduced into a polyester that exhibits biodegradability in a limited environment, thereby allowing the polyester to exhibit biodegradability in other environments as well. For example, Non-Patent Documents 1 and 2 report copolyester resins that have seawater degradability and thermal properties. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Polymer Degradation and Stability, 181, (2020), 109353 [Non-Patent Document 2] Polymer Degradation and Stability, 184, (2021), 109467 Summary of the Invention [Problem to be solved by the invention]
[0008] However, since the copolyester resins disclosed in Non-Patent Documents 1 and 2 are triblock copolymers, the seawater biodegradability of the copolyester resin depends on the molecular weight of the polylactic acid portion, which is a non-seawater degradable portion. Therefore, there are restrictions on the molecular weight when designing the copolyester resin. In addition, further improvements in thermoformability and biodegradability are required.
[0009] Therefore, an object of the present invention is to provide a copolyester resin having excellent thermoformability and biodegradability, and a method for producing the same. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved, and have completed the present invention having the following gist.
[0011] That is, the present invention includes the following aspects. [1] A block (X) derived from a polymer (x) having a biodegradable structural unit derived from a structure in which a dibasic acid (Ia) and a glycol (Ib) are bonded, and a block (Y) derived from a polymer (y) having a non-biodegradable structural unit derived from a structure in which a dibasic acid and a glycol are bonded, The copolyester resin is A triad unit (unit (A)) derived from a structure represented by "first glycol / dibasic acid / first glycol" in which a first glycol and a dibasic acid are bonded, and exhibits biodegradability; and a triad unit (unit (B)) derived from a structure represented by "second glycol / dibasic acid / second glycol" in which a second glycol different from the first glycol is bonded to a dibasic acid, and which exhibits biodegradability; In the copolyester resin, the triad mole fraction represented by the unit (A) is 0.01 or more, In the copolyester resin, the triad mole fraction represented by the unit (B) is 0.01 or more, A copolyester resin, wherein the sum of the triad mole fraction of the unit (A) and the triad mole fraction of the unit (B) is 0.05 or more. [2] The copolyester resin according to [1], wherein the biodegradable structural unit in the polymer (x) is represented by the following formula (3A) or the following formula (3B): [ka] Formula (3A) [ka] Formula (3B) (In formula (3A) and formula (3B), R3 represents a hydrogen atom or a methyl group, l and m each independently represent an integer of 0 to 4, l+m being 1 or greater, and n represents an integer of 4 to 8.) [3] The copolyester resin according to [1], wherein the dibasic acid (Ia) is at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid. [4] The copolyester resin according to [1], wherein the glycol (Ib) is at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol. [5] The biodegradable constitutional unit in the polymer (x) is A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded, A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol, diethylene glycol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded, The copolyester resin according to [1], which is at least one selected from the group consisting of: [6] The non-biodegradable structural unit in the polymer (y) is The copolyester resin according to [1], which is either a structural unit derived from a structure in which 1,4 butanediol and succinic acid are bonded together, or a structural unit derived from a structure in which 1,4 butanediol, adipic acid, and terephthalic acid are bonded together. [7] (i) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, adipic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, adipic acid, and 1,4 butanediol are bonded"; or (ii) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, sebacic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, sebacic acid, and 1,4 butanediol are bonded", or (iii) The copolyester resin according to [1], wherein the unit (A) is a triad unit derived from a "structure in which 3-methyl-1,5-pentanediol, adipic acid, and 3-methyl-1,5-pentanediol are bonded together" and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded together". [8] A method for producing the copolyester resin according to any one of [1] to [7], (i) synthesizing a polymer (x) having a biodegradable structural unit by polycondensing a dibasic acid and a glycol; synthesizing a polymer (y) having a non-biodegradable structural unit by polycondensing a dibasic acid and a glycol; A copolyester resin containing the block (X) and the block (Y) is produced by subjecting the polymer (x) and the polymer (y) to a transesterification reaction; or (ii) The dibasic acid and glycol used for synthesizing the polymer (x) having a biodegradable structural unit, and the dibasic acid and glycol used for synthesizing the polymer (y) having a non-biodegradable structural unit are polycondensed and subjected to an esterification reaction, a copolyester resin comprising the block (X) and the block (Y), [9] A resin composition comprising the copolyester resin according to any one of [1] to [7].
[10] A sheet or film made of the resin composition described in [9]. Effect of the Invention
[0012] According to the present invention, it is possible to provide a copolyester resin having excellent thermoformability and biodegradability, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The copolyester resin of the present invention will be described in detail below. However, the following description of the constituent elements is merely an example of one embodiment of the present invention, and the present invention is not limited to these contents.
[0014] (Copolyester resin) The copolyester resin of the present invention is derived from a structure in which a dibasic acid (Ia) and a glycol (Ib) are bonded, and comprises a block (X) derived from a polymer (x) having a biodegradable structural unit, and a block (Y) derived from a polymer (y) having a non-biodegradable structural unit derived from a structure in which a dibasic acid and a glycol are bonded, The copolyester resin is A triad unit (unit (A)) derived from a structure represented by "first glycol / dibasic acid / first glycol" in which a first glycol and a dibasic acid are bonded, and exhibits biodegradability; and a triad unit (unit (B)) derived from a structure represented by "second glycol / dibasic acid / second glycol" in which a second glycol different from the first glycol is bonded to a dibasic acid, and which exhibits biodegradability; In the copolyester resin, the triad mole fraction represented by the unit (A) is 0.01 or more, In the copolyester resin, the triad mole fraction represented by the unit (B) is 0.01 or more, the sum of the triad mole fraction of the unit (A) and the triad mole fraction of the unit (B) is 0.05 or more; It is a resin.
[0015] A substance being "biodegradable" means that, for example, when released into the natural environment, the substance is decomposed into carbon dioxide and water by the action of microorganisms, etc. Examples of "environments" in which a substance can be decomposed include seawater environments, freshwater environments, soil environments, and compost. However, in the present invention, particular attention is paid to biodegradability in a seawater environment. In the present invention, the term "biodegradable" refers to a seawater decomposition rate of 15% or more. On the other hand, in the present invention, "non-biodegradable" means that the seawater decomposition rate is less than 15%. In the present invention, the decomposition rate is specified as "seawater environment", but it does not exclude environments other than seawater environment. It is more preferable that the decomposition rate is 15% or more not only in the seawater environment but also in other environments such as freshwater environment, soil environment, or compost.
[0016] The copolyester resin of the present invention has excellent biodegradability and can be polymerized and thermoformed at a relatively high temperature similar to that of general-purpose resins. In other words, the copolyester resin of the present invention has excellent thermoformability and biodegradability. Furthermore, a sheet, film, etc. can be obtained by using a resin composition containing the copolyester resin.
[0017] An example of the presumed mechanism of action by which the excellent effects of thermoformability and biodegradability are remarkably obtained is shown below. The copolyester resin of the present invention is derived from a structure in which a dibasic acid (Ia) and a glycol (Ib) are bonded, and contains a block (X) derived from a polymer (x) having a structural unit exhibiting biodegradability. Cleavage of this block (X) site proceeds due to enzymes in the environment. As a result, the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the entire copolyester resin is biodegraded. Furthermore, the copolyester resin of the present invention contains a block (Y) derived from a polymer (y) having a structural unit exhibiting non-biodegradability and excellent thermoformability. As a result, the entire copolyester resin has excellent thermoformability. In addition to the above characteristics, the copolyester resin of the present invention further has the following characteristics: It contains a specific ratio of triad units (units (A)) derived from a structure represented by "first glycol / dibasic acid / first glycol" in which a first glycol and a dibasic acid are bonded, and triad units (units (B)) derived from a structure represented by "second glycol / dibasic acid / second glycol" in which a second glycol different from the first glycol is bonded to a dibasic acid, and also exhibiting biodegradability. By thus containing multiple types of biodegradable structural units in a well-balanced manner at a specific ratio, it is possible to ensure many sites where the cleavage of the biodegradable sites by enzymes in the environment can proceed, which leads to the promotion of biodegradability of the entire copolyester resin.
[0018] The components of the copolyester resin will be described below. The copolyester resin contains a block (X) derived from a polymer (x) and a block (Y) derived from a polymer (y). The polymer (x) is derived from a structure in which a dibasic acid (Ia) and a glycol (Ib) are bonded, and is a polymer having a structural unit that exhibits biodegradability. On the other hand, polymer (y) is derived from a structure in which a dibasic acid and a glycol are bonded, and is a polymer having a non-biodegradable structural unit.
[0019] <Polymer (x) Having a Biodegradable Structural Unit> Examples of the dibasic acid and glycol used in forming the polymer (x) include those shown below. The seawater decomposition rate of the structure obtained by binding varies depending on the combination of the types of dibasic acids and glycols. To form a biodegradable polymer (x), it is advisable to appropriately select preferred types from the dibasic acids and glycols exemplified below so that the structure obtained by binding exhibits a seawater decomposition rate of 15% or more.
[0020] <<Dibasic acid>> The dibasic acid is not particularly limited, but examples thereof include non-aromatic dicarboxylic acids, aromatic dicarboxylic acids, dicarboxylic anhydrides, halides, and esters thereof.
[0021] <<<Non-aromatic dicarboxylic acids>>> Examples of non-aromatic dicarboxylic acids include aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, unsaturated bond-containing non-aromatic dicarboxylic acids, etc. The number of carbon atoms in the non-aromatic dicarboxylic acid is not particularly limited, but is, for example, 3 to 15 carbon atoms.
[0022] Examples of the aliphatic dicarboxylic acid include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid. Examples of the alicyclic dicarboxylic acid include alicyclic dicarboxylic acids having 8 to 15 carbon atoms. Examples of alicyclic dicarboxylic acids include 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid. Examples of the unsaturated bond-containing non-aromatic dicarboxylic acid include maleic acid and fumaric acid.
[0023] <<<Aromatic dicarboxylic acids>>> Examples of aromatic dicarboxylic acids include aromatic dicarboxylic acids having 6 to 20 carbon atoms. More specific examples of aromatic dicarboxylic acids include orthophthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, and 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid.
[0024] Among these dibasic acids, from the viewpoint of biodegradability, non-aromatic dicarboxylic acids are preferred, aliphatic dicarboxylic acids are more preferred, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid represented by the following formula (1) are even more preferred, adipic acid, azelaic acid, and sebacic acid are even more preferred, and adipic acid and sebacic acid are particularly preferred. Two or more kinds of dibasic acids may be used in combination.
[0025] [ka] Formula (1) (In formula (1), n represents an integer of 4 to 8.)
[0026] <<Glycol>> The glycol may be a non-aromatic glycol or an aromatic glycol.
[0027] <<<Non-aromatic glycols>>> The non-aromatic glycol may be an aliphatic glycol or an alicyclic glycol, and the number of carbon atoms of the non-aromatic glycol may be, for example, 1 to 15.
[0028] Examples of aliphatic glycols include ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2-methylpentane-2,4-diol, 3,3-dimethyl-1,2-butanediol, 2,3-dimethyl-2,3-butanediol, butylethylpropanediol, 1,9-nonanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol.
[0029] Examples of the alicyclic glycol include alicyclic diols having a carbon number of 6 to 15. Examples of the alicyclic diol include 1,3-bis(2-hydroxypropyl)cyclopentane, 1,3-bis(2-hydroxybutyl)cyclopentane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(2-hydroxypropyl)cyclohexane, and 1,4-bis(2-hydroxybutyl)cyclohexane.
[0030] The aromatic glycol may, for example, be an aromatic glycol having 6 to 20 carbon atoms. Examples of aromatic glycols having 6 to 20 carbon atoms include 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-benzenediethanol, and 1,4-bis(2-hydroxyethoxy)benzene.
[0031] Among these glycols, from the viewpoint of biodegradability, non-aromatic glycols are preferred, aliphatic glycols are more preferred, and glycols represented by the following formula (2) are particularly preferred. Two or more types of glycols may be used in combination.
[0032] [ka] Formula (2) In formula (2), A represents a carbon atom or an oxygen atom, R1 represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms or a hydroxyl group, and R2 represents a hydrogen atom or a hydroxyl group. l and m each independently represent an integer of 0 to 4, provided that l+m is 1 or greater. However, when A is an oxygen atom, there is no H bonded to R1 or A. Also, either R1 or R2 is a hydroxyl group, but both R1 and R2 are not hydroxyl groups.
[0033] Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclopropyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, etc. Among these, a methyl group is preferred from the viewpoint of excellent reactivity.
[0034] Among the glycols represented by formula (2), 1,3-propanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-(2-hydroxyethoxy)ethanol, and 3-(3-hydroxypropoxy)propan-1-ol are preferred, and from the viewpoint of excellent biodegradability, 2-methyl-1,3-propanediol and 3-methyl-1,5-pentanediol are more preferred.
[0035] The biodegradable structural unit is derived from the structure, and the structure can be obtained by arbitrarily selecting the above dibasic acid and the above glycol, and subjecting them to an esterification reaction by a known method. Although not particularly limited, a suitable example of a biodegradable constitutional unit is, for example, a constitutional unit represented by the following formula (3A) or the following formula (3B).
[0036] [ka] Formula (3A)
[0037] [ka] Formula (3B) (In formula (3A) and formula (3B), R3 represents a hydrogen atom or a methyl group, l and m each independently represent an integer of 0 to 4, l+m being 1 or more, and n represents an integer of 4 to 8.)
[0038] In formula (3A), it is preferable that R3 is a methyl group, l and m are each independently an integer of 1 or 2, and n is an integer of 4-8.
[0039] To form a biodegradable polymer (x), it is preferable to use the dibasic acid (Ia) described below among the dibasic acids exemplified above. The dibasic acid (Ia) forming the biodegradable polymer (x) is preferably at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.
[0040] In order to form a biodegradable polymer (x), it is preferable to use the following glycol (Ib) among the glycols exemplified above. The glycol (Ib) forming the biodegradable polymer (x) is preferably at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol.
[0041] The structural unit exhibiting biodegradability in the polymer (x) is, A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded, A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol, diethylene glycol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded, It is preferable that the compound is at least one selected from the group consisting of the above.
[0042] Among these, the structural unit exhibiting biodegradability in the polymer (x) is More preferably, the structural unit is any one of a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, and a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded. Described in terms of specific structural formulas, examples include constitutional units represented by the following formulas (3-1) to (3-3), etc.
[0043] [ka] Formula (3-1)
[0044] [ka] Formula (3-2)
[0045] [ka] Formula (3-3)
[0046] <Polymer (y) Having a Non-biodegradable Structural Unit> The dibasic acids and glycols used to form the polymer (y) are as exemplified above in the section <Polymer (x) having a structural unit exhibiting biodegradability>. The seawater decomposition rate of the structure obtained by binding varies depending on the combination of the types of dibasic acids and glycols. Therefore, in order to form a non-biodegradable polymer (y), it is advisable to appropriately select preferred types from the dibasic acids and glycols exemplified above so that the structure obtained by binding exhibits a seawater decomposition rate of less than 15%. The non-biodegradable structural unit is not particularly limited, but preferably contains a structural unit derived from a structure in which a dibasic acid other than the dibasic acid represented by the above formula (1) described in the above section <Polymer (x) having a structural unit exhibiting biodegradability> is bonded to a glycol.
[0047] The non-biodegradable structural unit is not particularly limited, and examples thereof include structural units derived from butylene succinate, butylene adipate terephthalate, lactic acid, etc. Among these, it is preferable that the non-biodegradable structural unit in the polymer (y) is either a structural unit derived from butylene succinate represented by the following formula (4-1) (corresponding to a structural unit derived from a structure in which 1,4 butanediol and succinic acid are bonded) or a structural unit derived from butylene adipate terephthalate represented by the following formula (4-2) (a structural unit derived from a structure in which 1,4 butanediol, adipic acid, and terephthalic acid are bonded).
[0048] [ka] Formula (4-1)
[0049] [ka] Formula (4-2)
[0050] <Any polymer containing other structural units> The copolyester resin of the present invention may contain any polymer having other structural units than those described above, as necessary, within the scope of not impairing the effects of the present invention.
[0051] The copolyester resin of the present invention is a copolymer containing a block (X) and a block (Y), and is obtained by copolymerizing a polymer (x) having the above-mentioned biodegradable structural unit and a polymer (y) having the above-mentioned non-biodegradable structural unit. Although not particularly limited, suitable examples of the copolyester resin of the present invention include those represented by the following formulae (5) to (8).
[0052] [ka] Formula (5) (In formula (5), o, p, and q each independently represent a positive integer.)
[0053] [ka] Formula (6) (In formula (6), o, p, and q each independently represent a positive integer.)
[0054] [ka] Formula (7) (In formula (7), o, p, and q each independently represent a positive integer.)
[0055] [ka] Formula (8) (In formula (8), o, p, q and r each independently represent a positive integer.)
[0056] The content of the block (X) constituting the copolyester resin is preferably 5% by mass or more, more preferably 10% by mass or more, based on the copolyester resin (100% by mass), from the viewpoint of obtaining sufficient biodegradability. On the other hand, the content is preferably 50% by mass or less, more preferably 45% by mass or less, from the viewpoint of obtaining sufficient thermoformability. These upper and lower limits can be used in any combination. The content is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 45% by mass or less.
[0057] The content of the block (Y) constituting the copolyester resin is preferably 50% by mass or more, more preferably 55% by mass or more, based on the copolyester resin (100% by mass), from the viewpoint of obtaining sufficient thermoformability. On the other hand, the content is preferably 95% by mass or less, more preferably 90% by mass or less, from the viewpoint of obtaining sufficient biodegradability. These upper and lower limits can be used in any combination. The content is preferably 50% by mass or more and 95% by mass or less, more preferably 55% by mass or more and 90% by mass or less.
[0058] From the viewpoint of obtaining sufficient biodegradability, the molar ratio (X / Y) between block (X) and block (Y) is more than 5 / 95, preferably 10 / 90 or more, and more preferably 15 / 85 or more. On the other hand, from the viewpoint of obtaining sufficient thermoformability, the molar ratio (X / Y) is 95 / 5 or less, preferably 80 / 20 or less, and more preferably 70 / 30 or less. Any combination of these upper and lower limits can be used. The molar ratio (X / Y) is more than 5 / 95 and 95 / 5 or less, preferably 10 / 90 or more and 80 / 20 or less, and more preferably 15 / 85 or more and 70 / 30 or less.
[0059] The number average molecular weight (Mn) of the copolyester resin measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 5,000 or more, more preferably 7,000 or more, and even more preferably 8,000 or more, from the viewpoint of processability and handling. On the other hand, the number average molecular weight (Mn) is preferably 100,000 or less, more preferably 70,000 or less, and even more preferably 50,000 or less, from the viewpoint of obtaining sufficient biodegradability. These upper and lower limits can be used in any combination. The number average molecular weight (Mn) is preferably 5,000 or more and 100,000 or less, more preferably 7,000 or more and 70,000 or less, and even more preferably 8,000 or more and 50,000 or less.
[0060] The weight average molecular weight (Mw) of the copolyester resin measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 10,000 or more, more preferably 15,000 or more, and even more preferably 20,000 or more, from the viewpoint of processability and handling. On the other hand, the weight average molecular weight (Mw) is preferably 200,000 or less, more preferably 150,000 or less, and even more preferably 100,000 or less, from the viewpoint of obtaining sufficient biodegradability. These upper and lower limits can be used in any combination. The weight average molecular weight (Mw) is preferably 10,000 or more and 200,000 or less, more preferably 15,000 or more and 150,000 or less, and even more preferably 20,000 or more and 100,000 or less.
[0061] In the copolyester resin, the molecular weight distribution (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) in terms of polystyrene measured by GPC by the number average molecular weight (Mn) is preferably 4.5 or less, more preferably 4.0 or less, and even more preferably 3.7 or less, from the viewpoint of obtaining a resin having low dispersity and exhibiting desired properties.
[0062] The melting point (Tm) of the copolyester resin is preferably 40° C. or higher, more preferably 70° C. or higher, and even more preferably 100° C. or higher. On the other hand, the upper limit of the thermal decomposition temperature of the copolyester resin is not particularly limited, but is usually 250° C. or lower. When the melting point is within the above range, the thermal processability during molding is excellent.
[0063] The biodegradability of the copolyester resin in a seawater environment is 15% or more because the copolyester resin needs to exhibit the "biodegradability" defined in the present invention, but the seawater decomposition rate is more preferably 24% or more, even more preferably 40% or more, and particularly preferably 50% or more. In this specification, the biodegradability of the copolyester resin in a seawater environment is a value calculated by the following method. Inoculum source: Seawater collected from the coast of Akane Bay (near Akanehama, Narashino City, Chiba Prefecture) was used as the inoculum source. Biodegradability measurement method: Soda lime (carbon dioxide absorbent) and a pressure sensor (WTW, OxiTop-IDS (registered trademark)) are attached to a test bottle, and the BOD (biological oxygen demand) is measured under the conditions below to calculate the biodegradability. Culture temperature: 27℃, dark place Culture period: 28 days Calculation of biodegradation rate: The biodegradation rate of the sample is calculated based on the following formula. Biodegradation rate (%)=(BOD0-BOD B ) / ThOD×100 BOD0: Biochemical oxygen demand of the sample (measured value: mg) BOD B : Average biochemical oxygen demand in blank test (measured value: mg) ThOD: Theoretical oxygen demand required for complete oxidation of the sample (calculated value: mg)
[0064] The biodegradability of the copolyester resin in a freshwater environment is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more. In this specification, the biodegradability of the copolyester resin in a freshwater environment is a value calculated in the same manner as the seawater degradability described above, except that the inoculum source is river water collected from the Inagawa River (near Momozono, Ikeda City, Hyogo Prefecture).
[0065] The biodegradability of the copolyester resin in a soil environment is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more. In this specification, the biodegradability of the copolyester resin in a soil environment is a value calculated in the same manner as the seawater degradability described above, except that the inoculum source is soil collected from Oshinotsuka Community Farm (near Oshinotsuka, Sakura City, Chiba Prefecture).
[0066] The compost decomposition rate of the copolyester resin under composting conditions is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more. In this specification, the compost decomposition rate of the copolyester resin under compost conditions is a value determined by a method in accordance with JIS K6953-1:2011. Culture temperature: 58℃ Culture period: 28 days
[0067] <Copolyester resin having triad units of units (A) and units (B)> The copolyester resin of the present invention has two types of biodegradable triad units (units (A) and units (B)) in a desired ratio. Of the two types of biodegradable triad units contained in the copolyester resin of the present invention, one unit (unit (A)) is derived from a structure represented by "first glycol / dibasic acid / first glycol" in which a first glycol is bonded to a dibasic acid, and the other unit (unit (B)) is derived from a structure represented by "second glycol / dibasic acid / second glycol" in which a second glycol different from the first glycol is bonded to a dibasic acid. The units (A) and (B) are each contained in the copolyester resin of the present invention in a triad molar fraction of 0.01 or more, and the sum of the triad molar fractions of the units (A) and (B) must be 0.05 or more. By containing multiple types of biodegradable structural units in a balanced manner at specified ratios in this manner, it is possible to ensure that there are many sites at which the biodegradable moieties can be cleaved by enzymes in the environment, which leads to enhanced biodegradability of the entire copolyester resin.
[0068] The triad mole fraction can be calculated, for example, by the following method. -Identification of the resin's chemical structure- The chemical structure of the copolyester resin was analyzed by nuclear magnetic resonance ( 13 Identification is performed using C-NMR under the following conditions. Measurement equipment: JEOL RESONANCE "JNM-ECM400S" Magnetic field strength: 100MHz Number of times: 1000 Solvent: Deuterated chloroform Paramagnetic relaxation reagent: Chromium(III) acetylacetate. Sample concentration: 200mg / 1.0mL
[0069] -Calculation of triad mole fraction- Obtained 13 The C-NMR spectrum was subjected to waveform separation processing using JEOL Delta v5.3.1 software, and the triad peak integral value was calculated. The triad mole fraction is calculated based on the formula shown below. For example, the following formula shows a method for calculating the triad mole fraction for a triad unit derived from a structure represented by "2-methyl-1,3 propanediol (2MPD) / adipic acid (AA) / 1,4 butanediol (BG)". In the formula, SA of w represents succinic acid. M x-y-z =I x-y-z / (I x-y-z +I x-y―x +I z-y-z+I z-y-x +I x-w-z +I x-w-x +I z-w-z +I z-w-x ) M: triad mole fraction I: Triad peak integral value x:2MPD y:AA z:BG w:SA
[0070] Preferred combinations of the two types of biodegradable triad units (units (A) and units (B)) contained in the copolyester resin of the present invention include, for example, any of the following (i) to (iii). (i) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, adipic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, adipic acid, and 1,4 butanediol are bonded" or (ii) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, sebacic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, sebacic acid, and 1,4 butanediol are bonded", or (iii) It is preferable that the unit (A) is a triad unit derived from a "structure in which 3-methyl-1,5-pentanediol, adipic acid, and 3-methyl-1,5-pentanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded".
[0071] The requirements for the copolyester resin of the present invention will be explained below with reference to specific examples. The following example illustrates a copolyester resin obtained by transesterification of polymer (x) obtained by reacting 2-methyl-1,3 propanediol (2MPD) with adipic acid (AA) with polymer (y) obtained by reacting 1,4 butanediol (BG) with succinic acid (SA). The method for producing the copolyester resin will be described in detail in the section (Method for producing the copolyester resin) below.
[0072] <<First Specific Example of Copolyester Resin>> When 2-methyl-1,3-propanediol (2MPD) and adipic acid (AA) are subjected to a polycondensation reaction, a polymer (x) represented by the following formula (9) is obtained (see (Synthesis Example 1) in the following Examples).
[0073] [ka] Formula (9) (In formula (9), a represents a positive integer.) In the polymer (x) represented by formula (9), the constitutional unit represented by the following formula (3-1) is a constitutional unit derived from a structure in which 2MPD and AA are bonded, and is a constitutional unit that exhibits biodegradability.
[0074] [ka] Formula (3-1)
[0075] Next, 1,4-butanediol (BG) and succinic acid (SA) are subjected to a polycondensation reaction to obtain a polymer (y) represented by the following formula (10) (see (Synthesis Example 2) in the Examples below).
[0076] [ka] Formula (10) (In formula (10), b represents a positive integer.) In the polymer (y) represented by formula (10), the constitutional unit represented by the following formula (4-1) is a constitutional unit derived from a structure in which BG and SA are bonded, and is a constitutional unit that exhibits non-biodegradability.
[0077] [ka] Formula (4-1)
[0078] When the above polymer (x) and the above polymer (y) are subjected to an ester exchange reaction, a copolyester resin represented by the following formula (5) is obtained (see (Example 1) in the Examples below).
[0079] [ka] Formula (5) (In formula (5), o, p, and q each independently represent a positive integer.) The copolyester resin represented by formula (5) contains a block (X) represented by the above formula (3-1) derived from a polymer (x) and a block (Y) represented by the above formula (4-1) derived from a polymer (y).
[0080] The copolyester resin represented by the formula (5) obtained by the transesterification reaction of the polymer (x) and the polymer (y) has the following properties: A triad unit (A) derived from the structure represented by "2MPD / AA / 2MPD" and exhibiting biodegradability; - A triad unit derived from the structure represented by "BG / AA / BG" and may contain a triad unit (B) that indicates biodegradability, In the present invention, the units (A) and (B) are each contained in a triad mole fraction of 0.01 or more. Furthermore, the present invention specifies that the sum of the triad mole fractions of the units (A) and (B) is 0.05 or more. Here, for example, the unit (A) derived from the structure represented by "2MPD / AA / 2MPD" is represented by the following formula (A-1).
[0081] [ka] Formula (A-1) The triad mole fraction of the unit (A) represented by the above formula (A-1) is calculated as follows. M x-y-x =I x-y-x / (I x-y-x +I x-y―z +I z-y-z +I z-y-x +I x-w-z +I x-w-x +I z-w-z +I z-w-x ) M: triad mole fraction I: Triad peak integral value x:2MPD y:AA z:BG w:SA
[0082] (Method of producing copolyester resin) The copolyester resin of the present invention can be produced by a general method for producing a copolyester resin. However, in order to obtain a copolyester resin having two types of triad units (units (A) and units (B)) exhibiting biodegradability as specified in the present invention in a desired ratio, it is preferable to use a polyesterification reaction by a polyester exchange reaction or a polycondensation reaction described below.
[0083] <Production method of copolyester resin using polyester exchange method> The method for producing a copolyester resin of the present invention includes the steps of: synthesizing a polymer (x) having a biodegradable structural unit by polycondensing a dibasic acid and a glycol; A step of synthesizing a polymer (y) having a non-biodegradable structural unit by polycondensing a dibasic acid and a glycol; It is preferable to include a step of subjecting polymer (x) and polymer (y) to a transesterification reaction to produce a copolyester resin containing block (X) and block (Y).
[0084] <<Step of synthesizing polymer (x) and polymer (y)>> The synthesis method of the polymer (x) and the polymer (y) is not particularly limited, and can be carried out by using a general synthesis method of a polyester resin. Hereinafter, the case where the polymer (y) is a polyester resin containing a structural unit derived from a structure in which a dibasic acid other than the dibasic acid represented by the above formula (1) and a glycol are bonded will be described.
[0085] The dibasic acids and glycols used as raw materials in the synthesis of polymer (x) or polymer (y) can be the same as those exemplified above in the section entitled "Polymer (x) Having a Biodegradable Structural Unit." The raw materials for the synthesis of polymer (x) or polymer (y) may contain other raw materials in addition to the dibasic acid and glycol. The other raw materials are not particularly limited, but may include, for example, polyhydric alcohols having a valence of three or more, polyvalent carboxylic acids having a valence of three or more, and the like.
[0086] The blending ratio of the dibasic acid to the glycol is not particularly limited, but is preferably from 90:10 to 50:50, and more preferably from 80:20 to 50:50, in mass ratio (dibasic acid:glycol).
[0087] The reaction may be carried out without a catalyst or in the presence of a catalyst. Examples of the catalyst used in the reaction include acid catalysts. Examples of the acid catalyst include tin catalysts such as monobutyltin oxide and dibutyltin oxide, titanium catalysts such as titanium tetraisopropoxide and titanyl acetylacetonate, and zirconia catalysts such as tetra-butyl-zirconate. It is preferable to use a titanium catalyst in order to increase the activity of the transesterification reaction and the esterification reaction. Examples of the titanium catalyst include titanium tetramethoxide, titanium tetraethoxide, titanium tetraisopropoxide, titanium tetra n-propoxide, titanium tetra n-butoxide, tetrakis(2-ethylhexyloxy)titanium, and tetrastearyloxytitanium. In terms of stability in handling and activity as a catalyst, titanium tetraisopropoxide is preferred. The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the total mass of the dibasic acid and the glycol.
[0088] The reaction for synthesizing the polymer (x) or the polymer (y) generates by-products such as water and lower alcohols. These are removed from the reaction system during the reaction process, which makes it easier for the condensation reaction to proceed.
[0089] The reaction temperature is not particularly limited, but is usually 50 to 300°C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen gas or argon gas. The reaction time is usually 1 to 48 hours, but the reaction is preferably carried out until the dibasic acid or glycol as the raw material no longer remains in the reaction system. The progress of the reaction can be monitored, for example, by tracking the decrease in the dibasic acid by measuring the acid value.
[0090] <<Manufacturing process of copolyester resin by transesterification reaction>> The method for synthesizing a polymer by transesterification is not particularly limited, and can be carried out using a general method for synthesizing a polymer by transesterification.
[0091] The catalyst used in the transesterification reaction is preferably a titanium catalyst. Examples of the titanium catalyst include titanium tetramethoxide, titanium tetraethoxide, titanium tetraisopropoxide, titanium tetra n-propoxide, titanium tetra n-butoxide, tetrakis(2-ethylhexyloxy)titanium, and tetrastearyloxytitanium. In terms of stability in handling and activity as a catalyst, titanium tetraisopropoxide is preferred. The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the total mass of the polymer (x) and the polymer (y).
[0092] The reaction temperature is not particularly limited, but is usually 50 to 300° C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen gas or argon gas. The reaction time is usually 1 to 48 hours. In particular, in order to obtain a copolyester resin having two types of triad units (units (A) and units (B)) exhibiting biodegradability as specified in the present invention in a desired ratio, the reaction temperature is set to 150° C. and the reaction time is preferably 10 hours or more, more preferably 15 hours or more, even more preferably 20 hours or more, and particularly preferably 24 hours or more.
[0093] <Production method of copolyester resin using esterification method by polycondensation> The method for producing a copolyester resin of the present invention includes the steps of: preparing at least a dibasic acid and a glycol used for synthesizing a polymer (x) having a biodegradable structural unit; and preparing a dibasic acid and a glycol used for synthesizing a polymer (y) having a non-biodegradable structural unit; and a step of polycondensing these and subjecting them to an esterification reaction to produce a copolyester resin containing block (X) and block (Y).
[0094] <<Esterification step of polycondensing dibasic acid and glycol constituting polymer (x) and dibasic acid and glycol constituting polymer (y)>> The polycondensation of the dibasic acid and glycol constituting the polymer (x) and the dibasic acid and glycol constituting the polymer (y) is not particularly limited, and can be carried out using a general method for synthesizing polyester resins.
[0095] The dibasic acids and glycols used as raw materials in the synthesis of polymer (x) or polymer (y) can be the same as those exemplified above in the section entitled "Polymer (x) Having a Biodegradable Structural Unit." The raw materials for the synthesis of polymer (x) or polymer (y) may contain other raw materials in addition to the dibasic acid and glycol. The other raw materials are not particularly limited, but may include, for example, polyhydric alcohols having a valence of three or more, polyvalent carboxylic acids having a valence of three or more, and the like.
[0096] The blending ratio of the dibasic acid to the glycol is not particularly limited, but is preferably from 90:10 to 50:50, and more preferably from 80:20 to 50:50, in mass ratio (dibasic acid:glycol).
[0097] The reaction may be carried out without a catalyst or in the presence of a catalyst. Examples of the catalyst used in the reaction are as described above in the section "Method for producing a copolyester resin using a polyester exchange method."
[0098] In the esterification reaction in which a dibasic acid and a glycol are polycondensed, by-products such as water and lower alcohols are produced, but these are removed from the reaction system during the reaction process, which makes it easier for the condensation reaction to proceed.
[0099] The reaction temperature is not particularly limited, but is usually 50 to 300°C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen gas or argon gas. The reaction time is usually 1 to 48 hours, but the reaction is preferably carried out until the dibasic acid or glycol as the raw material no longer remains in the reaction system. The progress of the reaction can be monitored, for example, by tracking the decrease in the dibasic acid by measuring the acid value. In particular, in order to obtain a copolyester resin having two types of triad units (units (A) and units (B)) exhibiting biodegradability as specified in the present invention in a desired ratio, the reaction time is preferably 10 hours or more, more preferably 18 hours or more, and even more preferably 24 hours or more.
[0100] (Polyurethane) One embodiment of the copolyester resin obtained as described above is polyurethane. The polyurethane can be obtained by reacting the copolyester of the present invention with a polyisocyanate. If necessary, a polyol other than the copolyester, a chain extender, a chain terminator, or a crosslinking agent may be used in combination. Specifically, polyurethane is obtained by reacting a polyol with a polyisocyanate, and at least the copolyester of the present invention is used as the polyol. Thus, polyurethane is a reaction product obtained by reacting a polyol with a polyisocyanate, and polyurethane has structural units derived from the polyol and structural units derived from the polyisocyanate, and at least structural units derived from the copolyester of the present invention.
[0101] The copolyester of the present invention is preferably a polyester polyol. The polyester polyol may be a condensation polyester polyol. The condensation polyester polyol may be, for example, a reaction product of a low molecular weight polyhydric alcohol (ethylene glycol (EG), diethylene glycol, propylene glycol (PG), dipropylene glycol, (1,3- or 1,4-) butanediol, pentanediol, neopentyl glycol, hexanediol, cyclohexane dimethanol, glycerin, 1,1,1-trimethylolpropane (TMP), 1,2,5-hexanetriol, low molecular weight polyol such as pentaerythritol, sugar such as sorbitol, etc.) and a polybasic carboxylic acid (glutaric acid, adipic acid, azelaic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, terephthalic acid, isophthalic acid, dimer acid, pyromellitic acid, oligomer acid, etc.).
[0102] Examples of the chain extender include aliphatic polyol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, hexamethylene glycol, saccharose, methylene glycol, glycerin, sorbitol, and neopentyl glycol; bisphenol A, 4,4'-dihydroxydiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, hydrogenated bisphenol A, and hyaluronic acid. Aromatic polyol compounds such as hydroquinone; water; amine compounds such as ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, isophoronediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, aminoethylethanolamine, hydrazine, diethylenetriamine, and triethylenetetramine can be used. These chain extenders may be used alone or in combination of two or more. Among them, aliphatic polyol compounds are preferred, and neopentyl glycol is more preferred.
[0103] The content of the copolyester of the present invention in 100% by mass of polyol is preferably from 10 to 100% by mass, and more preferably from 50 to 100% by mass.
[0104] Examples of polyisocyanates include 1,3- and 1,4-phenylene diisocyanate, 1-methyl-2,4-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-2,5-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-3,5-phenylene diisocyanate, 1-ethyl-2,4-phenylene diisocyanate, 1-isopropyl-2,4 -phenylene diisocyanate, 1,3-dimethyl-2,4-phenylene diisocyanate, 1,3-dimethyl-4,6-phenylene diisocyanate, 1,4-dimethyl-2,5-phenylene diisocyanate, diethylbenzene diisocyanate, diisopropylbenzene diisocyanate, 1-methyl-3,5-diethylbenzene diisocyanate, 3-methyl-1,5-diethylbenzene-2,4-diisocyanate, 1,3,5- Triethylbenzene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 1-methyl-naphthalene-1,5-diisocyanate, naphthalene-2,6-diisocyanate, naphthalene-2,7-diisocyanate, 1,1-dinaphthyl-2,2'-diisocyanate, biphenyl-2,4'-diisocyanate, biphenyl-4,4'-diisocyanate, 3-3'-dimethylbiisocyanate Aromatic polyisocyanates such as phenyl-4,4'-diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, diphenylmethane-2,4-diisocyanate, and toluene diisocyanate; aliphatic polyisocyanates such as tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, and trimethylhexamethylene diisocyanate;Alicyclic polyisocyanates such as 1,3-cyclopentylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 1,3-di(isocyanatemethyl)cyclohexane, 1,4-di(isocyanatemethyl)cyclohexane, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, 2,2'-dicyclohexylmethane diisocyanate, and 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate can be used. These may be used alone or in combination of two or more. Among them, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, and toluene diisocyanate are more preferred.;
[0105] In order to control the molecular weight of the resulting polyurethane, a chain terminator having one active hydrogen group may be used as necessary. Examples of these chain terminators include aliphatic monohydroxy compounds having a hydroxyl group, such as methanol, ethanol, propanol, butanol, and hexanol, and aliphatic monoamines having an amino group, such as morpholine, diethylamine, dibutylamine, monoethanolamine, and diethanolamine. These may be used alone or in combination of two or more.
[0106] For the purpose of increasing the heat resistance and strength of the resulting polyurethane, a crosslinking agent having three or more active hydrogen groups or isocyanate groups can be used as necessary.
[0107] The polyurethane can be obtained by a known polyurethane manufacturing method. Specifically, for example, a manufacturing method can be mentioned in which a polyol, a polyisocyanate, and the chain extender are charged and reacted. These reactions are preferably carried out at a temperature of 50 to 100°C for 3 to 10 hours. The reaction may also be carried out in an organic solvent.
[0108] Examples of the organic solvent that can be used include ketone solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, methyl ethyl ketone, methyl-n-propyl ketone, acetone, and methyl isobutyl ketone; ester solvents such as methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, isopropyl acetate, isobutyl acetate, isobutyl acetate, and sec-butyl acetate; etc. These organic solvents may be used alone or in combination of two or more.
[0109] The content of the structural units derived from the copolyester of the present invention in 100% by mass of polyurethane is preferably from 10 to 98% by mass, and more preferably from 20 to 98% by mass. This tends to produce a more favorable effect. In this specification, the content of each structural unit in the polyurethane is measured by NMR.
[0110] The number average molecular weight (Mn) of the polyurethane may have a lower limit of 5,000 or more, 6,000 or more, 7,000 or more, 8,000 or more, or 10,000 or more, and an upper limit of 1,000,000 or less, 500,000 or less, 100,000 or less, 500,000 or less, or 15,000 or less. Any combination of these upper and lower limits may be used. The number average molecular weight (Mn) of the polyurethane may be 5,000 to 1,000,000, 6,000 to 500,000, 7,000 to 100,000, 8,000 to 500,000, or 10,000 to 15,000. Within the above range, the effect tends to be more favorably obtained.In this specification, the number average molecular weight (Mn) of the polyurethane is a value measured by GPC.
[0111] (Resin composition) Examples of the resin composition of the present embodiment include a thermoplastic resin composition containing the copolyester or polyurethane of the present embodiment described above, and a thermosetting resin composition.
[0112] <Thermoplastic resin composition> When the resin composition of the present embodiment is a thermoplastic resin composition, it may further contain, for example, other resins, a crystallization nucleating agent, a heat stabilizer, a hydrolysis inhibitor, other additives, and the like, as necessary.
[0113] <<Crystallization nucleating agent>> The crystallization nucleating agent used in the thermoplastic resin composition according to the present embodiment may be any crystallization nucleating agent used in thermoplastic resins derived from biomass resources, such as polylactic acid and polybutylene succinate. For example, talc-based nucleating agents, nucleating agents made of metal salt-based materials having a phenyl group, and nucleating agents made of benzoyl compounds are preferably used. Other known crystallization nucleating agents, such as lactate, benzoate, silica, and phosphate salts, may also be used.
[0114] <<Heat stabilizers and hydrolysis inhibitors>> The thermoplastic resin composition of the present embodiment preferably contains a phenol-based antioxidant and a phosphite-based antioxidant as a heat stabilizer for the resin composition, and a carbodiimide compound-based hydrolysis inhibitor, such as polycarbodiimide resin (product name: Carbodilite, manufactured by Nisshinbo Chemical Co., Ltd.), as a hydrolysis inhibitor. The heat stabilizer and hydrolysis inhibitor to be added may be one selected from the above three types of additives, but the above two types of heat stabilizers and hydrolysis inhibitors have different functions, and it is preferable that each additive is added together. The amount of heat stabilizer and hydrolysis inhibitor to be added varies depending on the type, but generally, it is preferable that each is about 0.1 to 5 parts by mass per 100 parts by mass of the thermoplastic resin composition.
[0115] <<Other additives>> It is preferable to further add a silicone-based flame retardant, an organometallic salt-based flame retardant, an organophosphorus-based flame retardant, a metal oxide-based flame retardant, a metal hydroxide-based flame retardant, etc. to the thermoplastic resin composition of this embodiment, which improves the flame retardancy and inhibits the spread of fire, and also improves the fluidity of the biodegradable resin composition, thereby ensuring better moldability.
[0116] A filler can be added to the thermoplastic resin composition of the present embodiment. Examples of the filler include talc, mica, montmorillonite, and kaolin. These fillers act as crystal nuclei to promote crystallization of the copolyester, improving the impact strength and heat resistance of the molded article. In addition, the rigidity of the molded article can be increased.
[0117] The thermoplastic resin composition of the present embodiment may be appropriately blended with various additives such as antioxidants, antiblocking agents, colorants, flame retardants, release agents, antifogging agents, surface wettability improvers, incineration aids, lubricants, dispersion aids, various surfactants, plasticizers, compatibilizers, weather resistance improvers, ultraviolet absorbers, processing aids, antistatic agents, colorants, lubricants, and release agents. As the plasticizer, any known plasticizer generally used as a plasticizer for polymers can be used without particular limitation, and examples thereof include polyester plasticizers, glycerin-based plasticizers, polyvalent carboxylic acid ester-based plasticizers, polyalkylene glycol-based plasticizers, and epoxy-based plasticizers. There are no particular limitations on the compatibilizer as long as it functions as a compatibilizer for copolymer A and copolymer B. Examples of the compatibilizer include inorganic fillers, glycidyl compounds, polymer compounds grafted or copolymerized with acid anhydrides, and organometallic compounds, and one or more of these may be used. By kneading these materials, the heat resistance, bending strength, impact strength, flame retardancy, etc. are improved, which further promotes the application of the materials to molded articles such as housings for electronic devices, such as notebook computers and mobile phones.
[0118] In addition, various fillers known in the art can be blended as the filler. As functional additives, chemical fertilizers, soil conditioners, plant activators, etc. can also be added. The fillers are broadly classified into inorganic fillers and organic fillers. These can be used alone or in a mixture of two or more kinds.
[0119] Examples of inorganic fillers include anhydrous silica, mica, talc, titanium oxide, calcium carbonate, diatomaceous earth, allophane, bentonite, potassium titanate, zeolite, sepiolite, smectite, kaolin, kaolinite, glass, limestone, carbon, wollastonite, calcined perlite, silicates such as calcium silicate and sodium silicate, hydroxides such as aluminum oxide, magnesium carbonate and calcium hydroxide, salts such as ferric carbonate, zinc oxide, iron oxide, aluminum phosphate and barium sulfate, etc. The content of the inorganic filler in the entire composition is usually 1 to 80% by weight, preferably 3 to 70% by weight, and more preferably 5 to 60% by weight. Examples of organic fillers include raw starch, processed starch, pulp, chitin, chitosan, coconut shell powder, wood powder, bamboo powder, bark powder, kenaf powder, straw powder, etc. These can be used alone or in a mixture of two or more. The amount of organic filler added is usually 0.01 to 70% by weight of the total composition.
[0120] The composition can be prepared by any of the conventionally known mixing / kneading techniques. As the mixer, a horizontal cylindrical type, V-shaped type, double cone type mixer, a blender such as a ribbon blender or a super mixer, or various continuous mixers can be used. As the kneader, a batch type kneader such as a roll or an internal mixer, a one-stage type or two-stage type continuous kneader, a twin screw extruder, a single screw extruder, or the like can be used. As the kneading method, a method of adding various additives, fillers, and thermoplastic resins to the heated and melted material and blending them can be mentioned. In addition, a blending oil or the like can be used for the purpose of uniformly dispersing the various additives.
[0121] <Thermosetting resin composition> When the resin composition of the present embodiment is a thermosetting resin composition, it contains, for example, another resin, the copolyester of the present embodiment having reactive groups such as a hydroxyl group or a carboxyl group as a thermosetting resin main component, and further contains a curing agent such as an isocyanate curing agent or a polyamine curing agent that can thermally react with the reactive groups.
[0122] Examples of the curing agent according to the present embodiment include polyisocyanates having an aromatic structure in their molecular structure, such as tolylene diisocyanate, diphenylmethane diisocyanate, polymeric diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and xylylene diisocyanate, and compounds in which a part of the isocyanate groups of these polyisocyanates is modified with carbodiimide; allophanate compounds derived from these polyisocyanates; polyisocyanates having an alicyclic structure in their molecular structure, such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexylisocyanate), and 1,3-(isocyanatomethyl)cyclohexane; linear aliphatic polyisocyanates, such as 1,6-hexamethylene diisocyanate, lysine diisocyanate, and trimethylhexamethylene diisocyanate, and allophane derivatives thereof. allophanate forms derived from these polyisocyanates; biuret forms derived from these polyisocyanates; trimethylolpropane-modified adducts; polyfunctional isocyanates such as polyisocyanates which are reaction products of the above-mentioned various polyisocyanates with polyol components; polyethylene polyamines such as ethylene diamine, diethylene triamine, triethylene tetramine, tetraethylene pentamine, pentaethylene hexamine, hexaethylene heptamine, heptaethylene octamine, octaethylene nonamine, nonaethylene decamine, piperazine, and N-aminoalkyl piperazines having an alkyl chain with 2 to 6 carbon atoms; and amine compounds such as 3-aminomethyl-3,5,5-trimethylcyclohexylamine (isophorone diamine, or IPDA).
[0123] <Cured product of resin composition> The cured product of the resin composition of the present embodiment is a cured product of the resin composition as the above-mentioned thermoplastic resin composition, or a cured product of the resin composition as the above-mentioned thermosetting resin composition.
[0124] The polymers described herein can be used in a wide variety of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, elastic fibers, urethane raw materials, automobile parts, sporting goods, vibration-proofing materials, vibration-damping materials, fiber treatment agents, and binders.
[0125] Copolyesters can be used in a wide range of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, elastic fibers, urethane raw materials, automotive parts, and sporting goods.
[0126] Polyurethane can be used in a wide range of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, vibration-proofing materials, vibration-damping materials, automobile parts, sporting goods, textile treatment agents, and binders.
[0127] (Coating agent) The coating agent contains the copolyester resin of the present invention, and further contains other components such as other resins, water, and organic solvents, as necessary.
[0128] The coating agent can be applied to various substrates. An example of the application of the coating agent will be described below. The coating agent is used, for example, for surface coating of the substrate of a food packaging container. Examples of the substrate include plastic films such as styrene-based resin films, polyolefin-based resin films, polyester-based resin films, nylon-based resin films, and laminates thereof. Examples of the substrate include paper, metal-deposited films, aluminum foils, and the like. The coating agent is preferably used for biodegradable substrates. Examples of the biodegradable substrate include paper, polyester-based films, polyolefin-based films, and starch-based films. The coating agent can be used as an ink, an adhesive, or the like.
[0129] (Ink) The ink contains the copolyester resin of the present invention and a colorant, and further contains other components such as a pigment dispersant, water, and an organic solvent, as necessary. The ink is, for example, a printing ink. The ink may be, for example, a water-based ink or an ink that does not contain water (solvent-based ink).
[0130] (glue) The adhesive contains the copolyester resin of the present invention, and further contains other components such as other resins, a curing agent, and an organic solvent, as necessary. The adhesive can also be used as an adhesive composition for lamination, which is laminated onto the various substrates described above to produce composite films used primarily as packaging materials for foods, medicines, detergents, and the like. Such adhesives include, for example, two-component curing adhesives containing the copolyester resin of the present invention, polyester polyol, and polyisocyanate, and one-component adhesives made of acrylic resin, urethane resin, and ethylene-vinyl acetate copolymer. These adhesives may be solvent-based, solventless, aqueous, or alcohol-based adhesives, as required.
[0131] (Sheet) The sheet is made of a resin composition containing the copolyester resin of the present invention. The resin composition may contain other resins and various additives in addition to the copolyester resin of the present invention. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and heat stabilizers. Examples of the sheet include a non-oriented sheet, a biaxially oriented sheet, and a foamed sheet. The uses of the sheet are not particularly limited, but it can be used in a wide range of applications, such as food packaging containers, construction materials, home electrical appliances, and miscellaneous goods.
[0132] (film) The film is made of a resin composition containing the copolyester resin of the present invention. The resin composition may contain other resins and various additives in addition to the copolyester resin of the present invention. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and heat stabilizers. Examples of the film include unstretched films, biaxially stretched films, and uniaxially stretched films, and can be produced by, for example, melting pellets of the film raw material in an extruder and forming the film into a film using a T-die or inflation method. In the T-die method, a biaxially stretched film is obtained by performing longitudinal stretching using the speed difference between rolls and transverse stretching using a tenter.
[0133] (Laminate) The laminate comprises at least one selected from the sheet and film of the present embodiment, and further comprises other components such as a printed layer and a resin film as necessary. The laminate can be obtained, for example, by laminating a film or sheet to one or both sides of at least one selected from the sheets and films of the present embodiment in order to improve mechanical strength, chemical resistance, etc. Specifically, the laminate can be obtained by thermally laminating a polystyrene-based inflation film to at least one of the front side and back side of the sheet or film, or by laminating an olefin-based film (CPP) using an adhesive. The adhesive used is not particularly limited, and may be, for example, the adhesive of the present embodiment or a known adhesive.
[0134] (Molded body) The molded article can be obtained by molding at least one selected from the sheet, film, and laminate of the present embodiment. The molded article can be obtained, for example, by thermoforming the sheet, film, or laminate of the present embodiment. Examples of the thermoforming method include hot plate contact heat molding, vacuum molding, vacuum pressure molding, and plug assist molding, and in particular, indirect heat molding using an infrared heater as a heat source is preferably used. EXAMPLES
[0135] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0136] <Chemical structure evaluation> In the examples and comparative examples, the chemical structure of the resin was determined by nuclear magnetic resonance ( 13 The compound was identified using C-NMR under the following conditions. Measurement equipment: JEOL RESONANCE "JNM-ECM400S" Magnetic field strength: 100MHz Number of times: 1000 Solvent: Deuterated chloroform Paramagnetic relaxation reagent: Chromium(III) acetylacetate. Sample concentration: 200mg / 1.0mL
[0137] <Calculation of triad mole fraction> Obtained 13 The C-NMR spectrum was subjected to waveform separation processing using JEOL Delta v5.3.1 software, and the triad peak integral value was calculated. The triad mole fraction in the unit (A) derived from the structure represented by "2MPD / AA / 2MPD" was calculated based on the formula shown below. M x-y-x =I x-y-x / (I x-y-x +I x-y―z +I z-y-z +I z-y-x +I x-w-z +I x-w-x +I z-w-z +I z-w-x ) M: triad mole fraction I: Triad peak integral value x:2MPD y:AA z:BG w:SA
[0138] <Evaluation of molecular weight> In the examples and comparative examples, the molecular weight of the resin was measured by gel permeation chromatography (GPC) under the following conditions. Measurement equipment: System controller Waters 600 Controller Liquid delivery pump Waters Model Code 60F RI (Differential Refractometer) Detector Waters 2414 Autosampler Waters 717plus Autosampler Data processing: Waters Empower3 Measurement conditions Measurement conditions: Column temperature 40℃ Eluent: Chloroform (CHCl3) Flow rate 1.0mL / min Standard: Polystyrene Column: Shodex GPC LF-G x 1 Shodex GPC LF-804 4 pieces Sample: 100 μL of a chloroform solution containing 0.4% by mass of resin solids filtered through a microfilter
[0139] <Oxidation evaluation> In the examples and comparative examples, the acid value of the resin was calculated according to the following procedure. Approximately 1 g of sample was weighed out and placed in a stoppered Erlenmeyer flask, and 20 mL of acetone was added to dissolve it. Phenolphthalein test solution was added as an indicator and the solution was left to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a pale pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL) F: Factor of 0.1N alcoholic potassium hydroxide solution
[0140] <Melting point measurement> Measurement equipment: Mettler DSC822 Measurement conditions: under nitrogen flow, temperature rise / fall rate 5℃ / min, measurement temperature range -60℃~180℃
[0141] <Evaluation of biodegradability> In the examples and comparative examples, the degree of biodegradation was calculated according to the following procedure, and the biodegradability was evaluated from the value of the degree of biodegradation.
[0142] <<Evaluation of seawater decomposition>> Inoculum source: Seawater collected from the coast of Akane Bay (near Akanehama, Narashino City, Chiba Prefecture) was used as the inoculum source. Biodegradability measurement method: Soda lime (carbon dioxide absorbent) and a pressure sensor (WTW, OxiTop-IDS (registered trademark)) were attached to a test bottle, and the BOD (biological oxygen demand) was measured under the conditions below to calculate the biodegradability. Culture temperature: 27℃, dark place Culture period: 28 days Calculation of biodegradability: The biodegradability of the resin samples of the Examples and Comparative Examples was calculated based on the following formula. Biodegradation degree (%)=(BOD0-BOD B ) / ThOD×100 BOD0: Biochemical oxygen demand of the sample (measured value: mg) BOD B : Average biochemical oxygen demand in blank test (measured value: mg) ThOD: Theoretical oxygen demand required for complete oxidation of the sample (calculated value: mg) Evaluation criteria: A (best): Biodegradability is 50% or more B (Excellent): Biodegradability is between 40% and 50% C (Good): Biodegradability is 24% or more but less than 40% D (Acceptable): Biodegradability is between 15% and 24% (lower practical limit) E (unacceptable): Biodegradability is less than 15% (not suitable for practical use)
[0143] <<Evaluation of freshwater degradability>> Degradability was evaluated in the same manner as described in the evaluation of seawater degradability, except that the inoculum source was river water collected from the Inagawa River (near Momozono, Ikeda City, Hyogo Prefecture).
[0144] <<Evaluation of soil decomposition>> Degradability was evaluated in the same manner as described for the evaluation of seawater degradability, except that the inoculum source was soil collected from Oshiozuka Community Farm (near Oshiozuka, Sakura City, Chiba Prefecture).
[0145] <<Evaluation of compost decomposition>> The compost decomposition rate was measured and compost decomposition was evaluated using a method in accordance with JIS K6953-1:2011. Culture temperature: 58℃ Culture period: 28 days Evaluation criteria: A (best): Compost decomposition rate is 50% or more B (Excellent): Compost decomposition rate is between 40% and 50% C (Good): Compost decomposition rate is between 24% and 40% D (Acceptable): Compost decomposition rate is between 15% and 24% (lower practical limit) E (unacceptable): Compost decomposition rate is less than 15% (not suitable for practical use)
[0146] (Synthesis Example 1) <Synthesis of poly(2-methyl-1,3 propanediol / adipic acid) (P(2MPD / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 396 parts by mass of 2-methyl-1,3 propanediol (2MPD), 604 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(2MPD / AA) was obtained. The structure of P(2MPD / AA) is shown in formula (9).
[0147] [ka] Formula (9) (In formula (9), a represents a positive integer.)
[0148] The biodegradability evaluation results showed that the biodegradability was 63% in seawater, 65% in freshwater, and 78% in soil, and the compost decomposition rate was 83%. The average molecular weight was measured to find that the number average molecular weight Mn was 10,071 and the weight average molecular weight Mw was 31,524.
[0149] (Synthesis Example 2) <Synthesis of poly(1,4 butanediol / succinic acid) (P(BG / SA))> P(BG / SA) was obtained in the same manner as in Synthesis Example 1, except that 441 parts by mass of 1,4-butanediol (BG), 559 parts by mass of succinic acid (SA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT) were used as raw materials and the temperature of the reaction liquid was set to 220° C. The structure of P(BG / SA) is shown in formula (10).
[0150] [ka] Formula (10) (In formula (10), b represents a positive integer.)
[0151] The biodegradability evaluation results showed that the biodegradability was 3% in seawater, 3% in freshwater, and 10% in soil, and the compost decomposition rate was 13%. The average molecular weight was measured, and the number average molecular weight Mn was 12,254, and the weight average molecular weight Mw was 28,416.
[0152] (Synthesis Example 3) <Synthesis of poly(2-methyl-1,3 propanediol / sebacic acid) (P(2MPD / SebA))> As raw materials, 322 parts by mass of 2-methyl-1,3 propanediol (2MPD), 678 parts by mass of sebacic acid (SebA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT) were used, and P(2MPD / SebA) was obtained in the same manner as in Synthesis Example 1. The structure of P(2MPD / SebA) is shown in formula (11).
[0153] [ka] Formula (11) (In formula (11), c represents a positive integer.)
[0154] The biodegradability evaluation results showed that the biodegradability was 65% in seawater, 65% in freshwater, and 74% in soil, and the compost decomposition rate was 83%. The average molecular weight was measured to find that the number average molecular weight Mn was 19,587 and the weight average molecular weight Mw was 63,356.
[0155] (Synthesis Example 4) <Synthesis of poly(3-methyl-1,5-pentanediol / adipic acid) (P(3MPD / AA))> As raw materials, 458 parts by mass of 3-methyl-1,5-pentanediol (3MPD), 542 parts by mass of adipic acid (AA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT) were used, and P(3MPD / AA) was obtained in the same manner as in Synthesis Example 1. The structure of P(3MPD / AA) is shown in formula (12).
[0156] [ka] Formula (12) (In formula (12), d represents a positive integer.)
[0157] The biodegradability evaluation results showed that the biodegradability was 63% in seawater, 64% in freshwater, and 78% in soil, and the compost decomposition rate was 85%. The average molecular weight was measured to find that the number average molecular weight Mn was 13,880 and the weight average molecular weight Mw was 42,954.
[0158] (Synthesis Example 5) <Synthesis of poly(1,4 butanediol / adipic acid / terephthalic acid) (P(BG / AA / tPA))> P(BG / AA / tPA) was obtained in the same manner as in Synthesis Example 1, except that the raw materials used were 398 parts by mass of 1,4-butanediol (BG), 292 parts by mass of adipic acid (AA), 332 parts by mass of terephthalic acid (tPA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT), and the temperature of the reaction liquid was set to 220° C. The structure of P(BG / AA / tPA) is shown in formula (13).
[0159] [ka] Formula (13) (In formula (13), e and f each independently represent a positive integer.)
[0160] The biodegradability evaluation results showed that the biodegradability was 3% in seawater, 3% in freshwater, and 8% in soil, and the compost decomposition rate was 10%. The average molecular weight was measured, and the number average molecular weight Mn was 26,445, and the weight average molecular weight Mw was 81,430.
[0161] (Synthesis Example 6) <Synthesis of poly(ethylene glycol / adipic acid) (P(EG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 306 parts by mass of ethylene glycol (EG), 694 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 190°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(EG / AA) was obtained. The structure of P(EG / AA) is shown in formula (14).
[0162] [ka] Formula (14) (In formula (14), a represents a positive integer.)
[0163] The biodegradability evaluation showed that the biodegradability was 50% in seawater, 52% in freshwater, and 55% in soil, and 65% in compost. The average molecular weight was measured, and the number average molecular weight Mn was 5568, and the weight average molecular weight Mw was 14619.
[0164] (Synthesis Example 7) <Synthesis of poly(diethylene glycol / adipic acid) (P(DEG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 431 parts by mass of diethylene ethylene glycol (DEG), 569 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(DEG / AA) was obtained. The structure of P(DEG / AA) is shown in formula (15).
[0165] [ka] Formula (15) (In formula (15), a represents a positive integer.)
[0166] The biodegradability evaluation showed that the biodegradability was 63% in seawater, 65% in freshwater, and 70% in soil, and the compost decomposition rate was 78%. The average molecular weight was measured, and the number average molecular weight Mn was 14,200 and the weight average molecular weight Mw was 102,600.
[0167] (Synthesis Example 8) <Synthesis of poly(1,2-propanediol / adipic acid) (P(1,2PG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 351 parts by mass of 1,2-propanediol (1,2PG), 649 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,2PG / AA) was obtained. The structure of P(1,2PG / AA) is shown in formula (16).
[0168] [ka] Formula (16) (In formula (16), a represents a positive integer.)
[0169] The biodegradability evaluation showed that the biodegradability was 71% in seawater, 67% in freshwater, and 75% in soil, and 81% in compost. The average molecular weight was measured to find that the number average molecular weight Mn was 6,870 and the weight average molecular weight Mw was 14,070.
[0170] (Synthesis Example 9) <Synthesis of poly(1,3-butanediol / adipic acid) (P(1,3BG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 391 parts by mass of 1,3-butanediol (1,3BG), 609 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 190°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, yielding P(1,3BG / AA). The structure of P(1,3BG / AA) is shown in formula (17).
[0171] [ka] Formula (17) (In formula (17), a represents a positive integer.)
[0172] The biodegradability evaluation showed that the biodegradability was 60% in seawater, 59% in freshwater, and 63% in soil, and 78% in compost. The average molecular weight was measured to find that the number average molecular weight Mn was 14,700 and the weight average molecular weight Mw was 92,000.
[0173] (Synthesis Example 10) <Synthesis of poly(1,3-propanediol / adipic acid) (P(1,3PG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 351 parts by mass of 1,3-propanediol (1,3PG), 649 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, yielding P(1,3PG / AA). The structure of P(1,3PG / AA) is shown in formula (18).
[0174] [ka] Formula (18) (In formula (18), a represents a positive integer.)
[0175] The biodegradability evaluation showed that the biodegradability was 47% in seawater, 49% in freshwater, and 55% in soil, and 68% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 5,540 and weight-average molecular weight Mw of 24,500.
[0176] (Synthesis Example 11) <Synthesis of poly(1,4-butanediol / adipic acid) (P(1,4BG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 391 parts by mass of 1,4-butanediol (1,4BG), 609 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, yielding P(1,4BG / AA). The structure of P(1,4BG / AA) is shown in formula (19).
[0177] [ka] Formula (19) (In formula (19), a represents a positive integer.)
[0178] The biodegradability evaluation showed that the biodegradability was 61% in seawater, 62% in freshwater, and 68% in soil, and 78% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 27,200 and weight-average molecular weight Mw of 132,000.
[0179] (Synthesis Example 12) <Synthesis of poly(1,5-pentanediol / adipic acid) (P(1,5PG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 426 parts by mass of 1,5-pentanediol (1,5PG), 574 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,5PG / AA) was obtained. The structure of P(1,5PG / AA) is shown in formula (20).
[0180] [ka] Formula (20) (In formula (20), a represents a positive integer.)
[0181] The biodegradability evaluation showed that the biodegradability was 63% in seawater, 65% in freshwater, and 67% in soil, and 76% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 6,210 and weight-average molecular weight Mw of 26,900.
[0182] (Synthesis Example 13) <Synthesis of poly(1,6-hexanediol / adipic acid) (P(1,6HD / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 458 parts by mass of 1,6-hexanediol (1,6HD), 542 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,6HD / AA) was obtained. The structure of P(1,6HD / AA) is shown in formula (21).
[0183] [ka] Formula (21) (In formula (21), a represents a positive integer.)
[0184] The biodegradability evaluation showed that the biodegradability was 55% in seawater, 54% in freshwater, and 62% in soil, and the compost decomposition rate was 68%. The average molecular weight was measured and found to be number average molecular weight Mn9634 and weight average molecular weight Mw30394.
[0185] (Synthesis Example 14) <Synthesis of poly(1,9-nonanediol / adipic acid) (P(1,9ND / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, rectification tube, and water separator, 535 parts by mass of 1,9-nonanediol (1,9ND), 465 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,9ND / AA) was obtained. The structure of P(1,9ND / AA) is shown in formula (22).
[0186] [ka] Formula (22) (In formula (22), a represents a positive integer.)
[0187] The biodegradability evaluation showed that the biodegradability was 58% in seawater, 57% in freshwater, and 65% in soil, and 75% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 4,410 and weight-average molecular weight Mw of 28,900.
[0188] Example 1 A glass vessel equipped with a stirrer and a nitrogen gas inlet tube was charged with 57 parts by mass of P(2MPD / AA) obtained in Synthesis Example 1, 443 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT), and the vessel was maintained at 200°C for 24 hours under a nitrogen stream to obtain a copolyester resin containing 2MPD / AA and BG / SA as structural units. The structure of the obtained copolyester resin is shown in formula (5).
[0189] [ka] Formula (5) (In formula (5), o, p, and q each independently represent a positive integer.)
[0190] The triad mole fractions of block X were 2MPD / AA / 2MPD 0.04 and BG / AA / BG 0.01, respectively, and the sum of them was 0.05. The biodegradability evaluation results showed that the biodegradability was 16% in seawater, 18% in freshwater, and 43% in soil, and the compost decomposition rate was 62%. The results of the biodegradability evaluation are shown in the following Table 1. Hereinafter, Table 1A and Table 1B will be collectively referred to as Table 1.
[0191] Example 2 In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, rectification tube, and water separator, 22 parts by mass of 2-methyl-1,3 propanediol (2MPD), 34 parts by mass of adipic acid (AA), 198 parts by mass of 1,4-butanediol (BG), 246 parts by mass of succinic acid (SA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen gas flow while maintaining the liquid temperature of the reaction liquid at 200°C and the steam temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2mgKOH / g or less, and a copolyester resin containing 2MPD / AA / BG / SA as structural units was obtained. The structure of the obtained copolyester resin is shown in formula (30).
[0192] [ka] Formula (30) (In formula (30), o, p, and q each independently represent a positive integer.)
[0193] The triad mole fractions of block X were 2MPD / AA / 2MPD 0.02 and BG / AA / BG 0.09, respectively, and the sum of them was 0.11. The results of the biodegradability evaluation are shown in Table 1 below.
[0194] (Examples 3 to 4) The same procedure as in Example 1 was carried out except that the amounts of P(2MPD / AA) and P(BG / SA) and the maintenance time as the reaction time were changed to the values shown in Table 1, to obtain a copolyester resin.
[0195] (Examples 5 and 6) The same procedure as in Example 2 was carried out except that the amounts of 2-methyl-1,3-propanediol (2MPD), adipic acid (AA), 1,4-butanediol (BG), and succinic acid (SA) used as raw materials were changed to the values shown in Table 1, to obtain a copolyester resin.
[0196] Example 7 A copolyester resin was obtained in the same manner as in Example 1, except that 195 parts by mass of P(2MPD / SebA) obtained in Synthesis Example 3, 305 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT) were charged as raw materials and the maintenance time, which is the reaction time, was changed to the value shown in Table 1. The structure of the obtained copolyester resin is shown in formula (6).
[0197] [ka] Formula (6) (In formula (6), o, p, and q each independently represent a positive integer.)
[0198] Example 8 A copolyester resin was obtained in the same manner as in Example 1, except that 181 parts by mass of P(3MPD / AA) obtained in Synthesis Example 4, 319 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT) were charged as raw materials and the maintenance time, which is the reaction time, was changed to the value shown in Table 1. The structure of the obtained copolyester resin is shown in formula (7).
[0199] [ka] Formula (7) (In formula (7), o, p, and q each independently represent a positive integer.)
[0200] Example 9 A copolyester resin was obtained in the same manner as in Example 1, except that 104 parts by mass of P(2MPD / AA) obtained in Synthesis Example 1, 390 parts by mass of P(BG / AA / tPA) obtained in Synthesis Example 5, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT) were charged as raw materials and the maintenance time, which is the reaction time, was changed to the value shown in Table 1. The structure of the obtained copolyester resin is shown in formula (8).
[0201] [ka] Formula (8) (In formula (8), o, p, q and r each independently represent a positive integer.)
[0202] Example 10 500 parts by mass of P(2MPD / AA / BG / SA) obtained in Example 6 was placed in a four-neck flask equipped with a thermometer, a stirrer, a nitrogen gas inlet, and a reflux condenser, and dissolved in 300 parts by mass of ethyl acetate to obtain an ethyl acetate solution of polyester polyol. 0.1 parts by mass of dibutyltin dilaurate (DBTDL) and 13 parts by mass of isophorone diisocyanate (IPDI) were added to the solution, and the reaction was carried out while maintaining the temperature at 70 to 80°C under a nitrogen stream. The reaction was terminated when the isocyanate weight ratio became less than 0.05% by mass, and a polyester urethane polyol solution was obtained.
[0203] Example 11 The same procedure as in Example 10 was carried out except that the raw material was changed to 10 parts by mass of hexamethylene diisocyanate (HDI), to obtain a polyester urethane polyol solution.
[0204] Example 12 The same procedure as in Example 10 was carried out except that the raw material was changed to 15 parts by mass of diphenylmethane diisocyanate (MDI), to obtain a polyester urethane polyol solution.
[0205] (Comparative Examples 1 to 3) The same procedure as in Example 1 was carried out except that the amounts of P(2MPD / AA) and P(BG / SA) and the maintenance time as the reaction time were changed to the values shown in Table 1, to obtain a copolyester resin.
[0206] Table 1 (Tables 1A and 1B) shows the reaction conditions and evaluation results of Examples 1 to 9 and Comparative Examples 1 to 3. Table 2 shows the reaction conditions and evaluation results of Examples 10 to 12.
[0207] [Table 1A]
[0208] [Table 1B]
[0209] [Table 2]
[0210] From the above examples, it was confirmed that the copolyester resin of the present invention has excellent thermoformability and biodegradability, whereas the resins of the comparative examples did not have such high biodegradability as the examples.
Claims
1. a block (X) derived from a polymer (x) having a structural unit exhibiting biodegradability, the block (X) being derived from a structure in which a dibasic acid (I-a) and a glycol (I-b) are bonded; and a block (Y) derived from a polymer (y) having a non-biodegradable structural unit derived from a structure in which a dibasic acid and a glycol are bonded, The copolyester resin is a triad unit (unit (A)) derived from a structure represented by "first glycol / diabasic acid / first glycol" in which a first glycol and a dibasic acid are bonded, and which exhibits biodegradability; and a triad unit (unit (B)) derived from a structure represented by "second glycol / dibasic acid / second glycol" in which a second glycol different from the first glycol is bonded to a dibasic acid, and which exhibits biodegradability; In the copolyester resin, the triad mole fraction represented by the unit (A) is 0.01 or more, In the copolyester resin, the triad mole fraction represented by the unit (B) is 0.01 or more, A copolyester resin, wherein the sum of the triad mole fraction of the unit (A) and the triad mole fraction of the unit (B) is 0.05 or more.
2. The copolyester resin according to claim 1, wherein the structural unit exhibiting biodegradability in the polymer (x) is represented by the following formula (3A) or the following formula (3B). 【Chemistry 1】 Formula (3A) 【Chemistry 2】 Formula (3B) (In formula (3A) and formula (3B), R 3 represents a hydrogen atom or a methyl group, l and m each independently represent an integer of 0 to 4, l+m being 1 or greater, and n represents an integer of 4 to 8.
3. 2. The copolyester resin according to claim 1, wherein the dibasic acid (Ia) is at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.
4. The copolyester resin according to claim 1, wherein the glycol (I-b) is at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol.
5. The biodegradable structural unit in the polymer (x) is A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded, A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol, diethylene glycol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded, The copolyester resin according to claim 1, which is at least one selected from the group consisting of:
6. The non-biodegradable structural unit in the polymer (y) is 2. The copolyester resin according to claim 1, which is either a structural unit derived from a structure in which 1,4 butanediol and succinic acid are bonded together, or a structural unit derived from a structure in which 1,4 butanediol, adipic acid, and terephthalic acid are bonded together.
7. (i) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3-propanediol, adipic acid, and 2-methyl-1,3-propanediol are bonded together," and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded together," or (ii) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3-propanediol, sebacic acid, and 2-methyl-1,3-propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, sebacic acid, and 1,4-butanediol are bonded", or (iii) The copolyester resin according to claim 1, wherein the unit (A) is a triad unit derived from a "structure in which 3-methyl-1,5-pentanediol, adipic acid, and 3-methyl-1,5-pentanediol are bonded together" and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded together".
8. A method for producing the copolyester resin according to any one of claims 1 to 7, comprising the steps of: (i) synthesizing a polymer (x) having a biodegradable structural unit by polycondensing a dibasic acid and a glycol; synthesizing a polymer (y) having a non-biodegradable structural unit by polycondensing a dibasic acid and a glycol; A copolyester resin containing the block (X) and the block (Y) is produced by subjecting the polymer (x) and the polymer (y) to a transesterification reaction; or (ii) The dibasic acid and glycol used for synthesizing the polymer (x) having a biodegradable structural unit, and the dibasic acid and glycol used for synthesizing the polymer (y) having a non-biodegradable structural unit are polycondensed and subjected to an esterification reaction, a copolyester resin comprising the block (X) and the block (Y),
9. A resin composition comprising the copolyester resin according to any one of claims 1 to 7.
10. A sheet or film comprising the resin composition according to claim 9.
Citation Information
Patent Citations
Biodegradable branched aromatic polyester-aliphatic polyester multi-block polymer
CN102344556A
Biodegradable branched aliphatic polyester multi-block copolymer and preparation method thereof
CN102516555A
Biodegradable polyester and its preparation method
CN102850533A
Polycarbonate resin composition and its resin molding
JP2012007034A
Copolyester resin and method for producing same
JP7605346B2